Treatment agents and painted metal materials
A treatment agent with specific compounds and ions forms a chemical conversion film on metal surfaces, addressing the inadequacy of existing pretreatment agents by significantly enhancing the corrosion resistance of coated metal materials.
Patent Information
- Application Number
- JP2019191827
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-10-21
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2039-10-21
AI Technical Summary
Existing pretreatment agents for chemical conversion treatments do not adequately enhance the corrosion resistance of coated metal materials.
A treatment agent comprising compounds with a specific structure and two or more primary amino groups, along with molybdate or tungstate ions, is used to form a chemical conversion film on metal surfaces, incorporating amphoteric metals like zinc, aluminum, or lead, with molybdenum and/or tungsten in the lower layer of the film.
The solution significantly improves the corrosion resistance of coated metal materials by forming a protective chemical conversion film that enhances the durability and resistance to environmental degradation.
Smart Images

Figure 0007602865000001 
Figure 0007602865000002 
Figure 0007602865000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a treating agent used in pretreatment for chemical conversion treatment to form a chemical conversion coating on the surface or surface of a metal material, and to a coated metal material having a chemical conversion coating and a paint film. [Background technology]
[0002] Conventionally, various chemical conversion coating agents and surface treatment agents have been developed to improve the corrosion resistance of coated metal materials. For example, Patent Document 1 discloses a pretreatment agent for metal materials used in pretreatment for chemical conversion coating, which is a blend of a specific polymer and water. Furthermore, Patent Document 2 discloses a method for anti-corrosion pretreatment of a metal surface including steel, galvanized steel, aluminum, magnesium, and / or a zinc-magnesium alloy, which comprises contacting the metal surface with an aqueous composition A containing a specific amount of a copolymer containing specific monomer units, and an acidic aqueous composition B containing at least one compound selected from the group consisting of titanium, zirconium, and hafnium compounds. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2019 / 087320 [Patent Document 2] Special Publication No. 2019-518874 Summary of the Invention [Problem to be solved by the invention]
[0004] Although the above pretreatment agents have been proposed to improve the corrosion resistance of coated metal materials, there is a need to develop other means. An object of the present invention is to provide a new means for improving the corrosion resistance of coated metal materials. [Means for solving the problem]
[0005] As a result of intensive research into solving the above problems, the inventors have found that by carrying out a pretreatment before chemical conversion treatment using a treatment agent containing a compound (A) having a specific structure and containing two or more primary amino groups, and a specific metal ion (B), a metal material having a coating film formed after the chemical conversion treatment has excellent corrosion resistance, and have completed the present invention.
[0006] The means for solving the above problems are as follows. [1] A treatment agent used in pretreatment of a chemical conversion treatment for forming a chemical conversion coating on the surface or surface of a metal material, the treatment agent comprising: One or more compounds (A) selected from compounds having a structure represented by the following formula (I) and having two or more primary amino groups; a metal acid ion (B) selected from a molybdate ion and a tungstate ion; A treatment agent comprising: -(NH-CH2-CH2) n - (I) Here, n is an integer of 1 or more. [2] A metal material having a chemical conversion coating on or at the surface of the metal material, one or more amphoteric metals selected from the group consisting of zinc, aluminum, tin, and lead are present on the surface of the metal material coated with the chemical conversion coating; A metal material having a chemical conversion coating, the chemical conversion coating comprising the amphoteric metal and molybdenum and / or tungsten, the molybdenum and / or tungsten being present in an underlying layer of the chemical conversion coating. [3] A coated metal material having a coating film on the surface of the metal material having the chemical conversion coating according to [2]. Fee. Effect of the Invention
[0007] According to the present invention, it is possible to provide a new pretreatment agent capable of improving corrosion resistance when a coating film is formed, and a technique such as a pretreatment method for chemical conversion coating using the pretreatment agent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The treatment agent according to the embodiment of the present invention is a treatment agent used in a pretreatment carried out prior to a chemical conversion treatment for forming a chemical conversion coating on the surface or surface of a metal material. The treatment agent contains one or more compounds (A) selected from compounds having a structure represented by the following formula (I) and having two or more primary amino groups, and metal acid ions (B) selected from molybdate ions and tungstate ions. -(NH-CH2-CH2) n - (I) Here, n is an integer of 1 or more. The treatment agent according to this embodiment, the method for producing the treatment agent, the method for treating and producing a metal material with the treatment agent, the method for chemical conversion treatment after pretreatment, the metal material having a chemical conversion coating formed by chemical conversion treatment, the method for producing a coated metal material including a coating step for coating the surface of the metal material having a chemical conversion coating, and the coated metal material having a coating film on the surface of the metal material having a chemical conversion coating will be described below in order. Note that the present invention can be modified as desired within the scope of the gist of the invention, and is not limited to the specific embodiments described below.
[0009] <Compound (A)> Compound (A) is selected from compounds having a structure represented by the following formula (I) and having two or more primary amino groups. -(NH-CH2-CH2) n - (I) In formula (I), n is an integer of 1 or more, may be an integer of 2 or more, or may be an integer of 3 or more. The upper limit of n is not particularly limited, but is usually 10 or less, and may be 5 or less. Alternatively, compound (A) may be a compound represented by the following formula (II): [ka] In formula (II), n is an integer of 1 or more, may be an integer of 2 or more, or may be an integer of 3 or more. The upper limit of n is not particularly limited, but is usually 10 or less, and may be 5 or less. R1, R2, ..., Rn are independently H, an alkyl group (having 1 to 3 carbon atoms), or a group containing at least one ethyleneamine unit. "···" is absent when n=1, represents a single bond when n=2, and represents a repetition of the unit represented in parentheses when n=3 or more. R 2 is H or -(CH2) m NH2 (m is an integer between 1 and 3). R 3 is H, -(CH2) m NH2 (m is an integer of 1 to 3), or a primary amino group. Compound (A) is preferably a compound having the structure represented by the above formula (I) and having two primary amino groups, more preferably a compound having a linear structure and two primary amino groups at both ends.
[0010] Examples of the compound (A) include ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, N,N'-bis(2-methylphenyl)amine, and the like. Examples include (2-aminoethyl)-1,3-propanediamine, N,N'-bis(3-aminopropyl)ethylenediamine, polyethyleneimine, hexaethyleneheptamine, heptaethyleneoctamine, nonaethylenedecamine, etc. These may be used alone or in combination of two or more.
[0011] The content of compound (A) in the treatment agent is not particularly limited, but is within the range of 1 to 20,000 mg / L, and preferably within the range of 5 to 10,000 mg / L, in terms of solid content mass. The molecular weight of the compound (A) is not particularly limited, but when it is a polymer compound such as polyethyleneimine, the weight average molecular weight may be about 300 to 100,000. The weight average molecular weight is a value measured by GPC (gel permeation column chromatography) and converted into polystyrene.
[0012] <Metal acid ion (B)> The metal acid ion (B) is an ion selected from a molybdate ion and a tungstate ion. The source of the metal acid ion (B) is not particularly limited as long as it can provide the metal acid ion (B) by mixing with an aqueous medium. For example, sodium molybdate, ammonium molybdate, potassium molybdate, lithium molybdate, calcium molybdate, sodium tungstate, ammonium tungstate, potassium tungstate, lithium tungstate, calcium tungstate, etc. may be mentioned. These may be used alone or in combination of two or more. The content of the metal acid ion (B) in the treatment agent is not particularly limited, but is usually within the range of 0.01 to 1000 mmol / L, and preferably within the range of 0.1 to 500 mmol / L, calculated as molybdenum and / or tungsten.
[0013] The pH of the treatment agent according to the present embodiment is not particularly limited, but is usually 7.0 or more, may be 8.0 or more, may be 9.0 or more, and is usually 12.0 or less, may be 11.0 or less, may be 10.0 or less. Here, the pH in this specification is a value measured for the treatment agent at 25°C using a pH meter. In order to set the pH of the treatment agent in the above range, a pH adjuster may be used. The pH adjuster that can be used when it is desired to increase the pH is not particularly limited, but for example, an aqueous solution of sodium hydroxide, an aqueous solution of potassium hydroxide, ammonia water, triethanolamine, triethylamine, etc. are preferable. On the other hand, the pH adjuster that can be used when it is desired to decrease the pH is not particularly limited, but for example, formic acid, acetic acid, nitric acid, lactic acid, methanesulfonic acid, etc. are preferable. It should be noted that one or more of these pH adjusters may be used.
[0014] The treatment agent according to the present embodiment is prepared as a liquid. The method for producing the liquid is not particularly limited, but for example, the liquid can be prepared by mixing the compound (A) and the source of the metal acid ion (B) in water. The liquid medium is not particularly limited, but water (deionized water, distilled water) is preferable. In addition, as the liquid medium, a mixed solvent obtained by mixing a hydrophilic solvent (e.g., a lower alcohol) in water may be used as long as the compound (A) and the source of the metal acid ion (B) can be dissolved or dispersed therein.
[0015] When a metal material is pretreated using the treatment agent according to this embodiment, the metal material may dissolve and metal components may be mixed into the treatment agent. For this reason, the treatment agent may contain metal components such as Fe, Zn, Al, and Mg. The same applies to components that are inevitably mixed in during operation, such as Zr. These components may be unavoidably mixed into the treatment agent, or may be intentionally included in the treatment agent. Examples of counter ions sourced from the compound for adjusting the metal components and acid components sourced from the acid compound for adjusting pH include carbonate ions, nitrate ions, silicate ions, and sulfonate ions, which are mixed in as anion components of acids or salts. You may do so.
[0016] (Method for pre-treating metal materials and method for manufacturing metal materials) Another embodiment of the present invention relates to a method for pretreating a metal material, which includes a step of contacting the above-mentioned treatment agent with a metal material (hereinafter also referred to as a pretreatment step).The present invention also relates to a method for producing a metal material, which includes a step of contacting the above-mentioned treatment agent with a metal material.
[0017] The pretreatment method or manufacturing method of a metal material includes a pretreatment step of contacting the treatment agent according to the embodiment of the present invention with the surface or on the surface of the metal material. The pretreatment method or manufacturing method of a metal material may include washing the metal material with water after the pretreatment step. In addition, a degreasing step, which is called degreasing and removes oil and deposits from the surface of the metal material, may be included before the pretreatment step. The degreasing step is not particularly limited, and a known method can be applied. Washing with water may or may not be performed after the degreasing step. In addition, the pretreatment step may include pickling and / or oxide film removal, which is called pickling and removes iron oxide and zinc oxide from the surface of the metal material. The method of pickling and / or oxide film removal is not particularly limited, and a known method can be applied.
[0018] The contact method of the treatment agent may be a known contact method, such as a dipping treatment method, a spraying treatment method, a pouring treatment method, or a combination thereof. The contact with the treatment agent is preferably carried out at a predetermined temperature for a certain period of time. The contact temperature is preferably 5°C or higher and 60°C or lower, and more preferably 10°C or higher and 50°C or lower, but is not limited to these temperatures. The contact time is preferably 5 to 600 seconds, and more preferably 10 to 300 seconds, but is not limited to these treatment times.
[0019] Another embodiment of the present invention relates to a method for producing a metal material having a chemical conversion coating, which includes a chemical conversion treatment step of contacting the surface of the metal material with the above-mentioned treatment agent and then forming a chemical conversion coating on the metal material. The present invention also relates to a metal material having a chemical conversion coating obtained by the method. The chemical conversion treatment step is not particularly limited as long as it is a treatment for forming a chemical conversion coating, and examples thereof include a zirconium chemical conversion treatment step, a titanium chemical conversion treatment step, a hafnium chemical conversion treatment step, and a vanadium chemical conversion treatment step. The above-mentioned various chemical conversion treatment steps may be performed alone, or two or more steps may be combined and performed sequentially. In addition, when two or more steps are combined, water washing may or may not be performed after each post-process, or some water washing may be omitted. The treatment temperature and contact time in the chemical conversion treatment step can be appropriately set depending on the type of chemical conversion treatment step, the concentration of the chemical conversion treatment agent, etc.
[0020] Another embodiment of the present invention relates to a method for producing a coated metal material, which includes a coating step of coating the surface of the metal material having the above-mentioned chemical conversion coating. The present invention also relates to a coated metal material having a coating film on the surface of the metal material having the above-mentioned chemical conversion coating obtained by the above-mentioned manufacturing method. The coating method is not particularly limited, and known methods such as rolling coating, electrodeposition coating (e.g., cationic electrodeposition coating), spray coating, hot spray coating, airless spray coating, electrostatic coating (e.g., electrostatic powder coating), roller coating, curtain flow coating, brush coating, bar coating, and fluidized bed immersion method can be applied. After the coating step, a drying step (including a baking step and a curing step) for drying the paint on the surface of the coated metal material may be performed. Furthermore, the surface of the metal material having the chemical conversion coating may or may not be washed with water before the coating step, and the surface of the metal material after washing with water or before not being washed with water may or may not be dried before the coating step.
[0021] Examples of the paint include oil-based paint, cellulose derivative paint, phenolic resin paint, alkyd resin paint, aminoalkyd resin paint, urea resin paint, unsaturated resin paint, vinyl resin paint, etc. Examples of the paint include known paints such as paint, acrylic resin paint, epoxy resin paint, polyurethane resin paint, silicon resin paint, fluororesin paint, rust-preventive paint, antifouling paint, powder paint, cationic electrodeposition paint, anionic electrodeposition paint, water-based paint, and solvent-based paint. The coating process may involve one coating or two or more coatings using the same or different paints. The drying process is a process for drying and curing the applied paint. Examples of the drying method include natural drying, reduced pressure drying, convection-type heat drying (e.g., natural convection-type heat drying, forced convection-type heat drying), radiation-type drying (e.g., near-infrared drying, far-infrared drying), ultraviolet curing drying, electron beam curing drying, vapor curing, and baking drying. These drying methods may be carried out alone or in combination of two or more.
[0022] A known method can be applied to the cationic electrodeposition coating. For example, a cationic electrodeposition coating containing an amine-added epoxy resin and a blocked polyisocyanate curing agent as a curing component is used as the coating material, and a method of immersing a metal material having a chemical conversion coating in the coating material can be mentioned. The cationic electrodeposition coating is carried out, for example, by applying a voltage to a metal material having a chemical conversion coating in the cathode direction using a rectifier while maintaining the temperature of the coating material at a predetermined temperature and stirring the coating material. The metal material thus subjected to cationic electrodeposition coating can be washed with water and baked to form a coating film on the chemical conversion coating. The baking is carried out for a certain period of time at a predetermined temperature range. Specifically, it is carried out at 170°C for 20 minutes. When applying a cationic electrodeposition coating method using a cationic electrodeposition coating, for example, it is preferable to control the sodium ion concentration in the treatment agent used in the degreasing process, pretreatment process, various chemical conversion treatment processes, etc. to less than 500 ppm by mass.
[0023] Known methods can be used for coating the powder paint, such as spray coating, electrostatic powder coating, and fluidized bed immersion. Examples of the powder paint include those containing polyester resin and a curing agent such as a blocked isocyanate curing agent, a β-hydroxyalkylamide curing agent (see, for example, JP 2011-88083 A) or triglycidyl isocyanurate. Baking is performed for a certain period of time at a predetermined temperature range. Specifically, baking is performed at 150 to 250°C for 20 minutes.
[0024] As a coating method such as spray coating, electrostatic coating, bar coating, etc., using the above-mentioned solvent paint, a known method can be applied. Examples of the solvent paint include those containing resins such as melamine resin, acrylic resin, urethane resin, polyester resin, etc., and organic solvents such as thinner. Baking is performed for a certain period of time at a predetermined temperature range. Specifically, it is performed at 130°C for 20 minutes.
[0025] The coating film obtained by the coating process may be a single layer or multiple layers. In the case of multiple layers, the paints for forming the various coating films, the coating method using the paints, the drying method of the coated metal material, etc. may be the same or different.
[0026] In this embodiment, the type of metal material that can be used as the target of the pretreatment process is not particularly limited. Examples include steel materials (e.g., cold-rolled steel sheets, hot-rolled steel sheets, high-tensile steel sheets, tool steels, alloy tool steels, spheroidized graphite cast iron, gray cast iron, etc.); plated materials, such as zinc-plated materials (e.g., electrolytic zinc plating, hot-dip galvanizing, etc.), zinc alloy-plated materials (e.g., alloyed hot-dip galvanizing, Zn-Al alloy plating, Zn-Al-Mg alloy plating, electrolytic zinc alloy plating, etc.), aluminum-plated materials, etc.; aluminum materials or aluminum alloy materials (e.g., 1000 series, 2000 series, 3000 series, 4000 series, 5000 series, 6000 series, aluminum castings, aluminum alloy castings, die-cast materials, etc.); magnesium materials or magnesium alloy materials; zinc materials, such as pure zinc materials, zinc alloy materials; tin materials, such as pure tin materials, tin alloy materials; lead materials, such as pure lead materials, lead alloy materials.
[0027] The metal material having a chemical conversion coating can be produced by the above-mentioned method for producing a metal material having a chemical conversion coating. Examples of the chemical conversion coating include a zirconium chemical conversion coating, a titanium chemical conversion coating, a hafnium chemical conversion coating, and a vanadium chemical conversion coating. The chemical conversion coating may be one layer or two or more layers. Here, when a zirconium chemical conversion coating, a titanium chemical conversion coating, and / or a hafnium chemical conversion coating is formed, the mass of the formed chemical conversion coating is 5 mg / m2 in terms of the mass of zirconium, titanium, hafnium, or vanadium in the chemical conversion coating per unit area of the metal material surface. 2 More than 500mg / m 2 Preferably, it is 10 mg / m or less. 2 More than 250mg / m 2 It is more preferable that the content of the metal is equal to or less than 100%, but the present invention is not limited to this range. When two or more metals are contained, the total content of the metals is preferably within the above range.
[0028] The amount of zirconium, titanium, hafnium, or vanadium in a chemical conversion coating such as a zirconium chemical conversion coating, a titanium chemical conversion coating, a hafnium chemical conversion coating, or a vanadium chemical conversion coating can be measured by dissolving the chemical conversion coating in concentrated nitric acid and then performing ICP emission spectrometry, or by analyzing a metal material having a chemical conversion coating by X-ray fluorescence analysis.
[0029] The coated metal material can be manufactured by the above-mentioned method for manufacturing a coated metal material. Here, the coating film formed on the coated metal material may be a single layer or multiple layers. In the case of multiple layers, the paint, coating method, drying method, etc. of each layer may be the same or different. The thickness of the coating film may be thick, exceeding 100 μm, or thin, less than 5 μm. For example, in the case of electrodeposition coating, the coating film is generally applied to a thickness of about 10 to 30 μm, but it may be thick, such as 100 μm, or thin, such as 3 μm.
[0030] Another embodiment of the present invention is a metal material having a conversion coating on or at a surface of the metal material, one or more amphoteric metals selected from the group consisting of zinc, aluminum, tin, and lead are present on the surface of the metal material coated with the chemical conversion coating; The chemical conversion coating comprises the amphoteric metal and molybdenum and / or tungsten, the molybdenum and / or tungsten being present in an underlying layer of the chemical conversion coating, and is a metal material having a chemical conversion coating.
[0031] In this embodiment, the metal material has at least one amphoteric metal selected from the group consisting of zinc, aluminum, tin and lead on its surface, that is, at least the surface coated with the chemical conversion coating. The chemical conversion coating on the metal material contains an amphoteric metal contained in the metal material, and molybdenum and / or tungsten. The amphoteric metal contained in the chemical conversion coating originates from the amphoteric metal contained in the metal material, and is therefore inevitably mixed in, but it may be intentionally included in the chemical conversion coating, and the form thereof is not limited.
[0032] Molybdenum and / or tungsten are not uniformly present in the chemical conversion coating, but are present in the lower layer of the chemical conversion coating. The molybdenum and / or tungsten present can typically be formed in a layer in the cross section of the metal material having the chemical conversion coating. When it is layered, the thickness is usually 1 nm or more, and may be 2 nm or more, and is usually 100 nm or less, and may be 50 nm or less, or may be 10 nm or less. As for the form of the molybdenum and / or tungsten present in the lower layer of the chemical conversion coating, when molybdenum and / or tungsten are present in a layered form, the molybdenum and / or tungsten layer may be located closer to the metal material than the center of the chemical conversion coating in the thickness direction of the chemical conversion coating, may be located within 25% closer to the metal material in the chemical conversion coating, may be located within 15% closer to the metal material in the chemical conversion coating, may be located within 10% closer to the metal material in the chemical conversion coating, or may be laminated with the metal material. Molybdenum and / or tungsten may be present in the conversion coating under the conversion coating. This can be distinguished by observing the cross section using SEM-EDS or the like.
[0033] The chemical conversion coating may contain other components in addition to the amphoteric metal contained in the metal material, and molybdenum and / or tungsten. The other components are not particularly limited as long as they are components capable of forming a chemical conversion coating, and examples of such components include compounds consisting of one or more selected from C, N, O, and H, and such compounds may be resins, etc. In addition, the chemical conversion coating may contain a silane compound.
[0034] The thickness of the chemical conversion coating is not particularly limited, but when a cross section of a metal material having the chemical conversion coating is measured, the thickness is usually 5 nm or more, and may be 10 nm or more, and is usually 1000 nm or less, and may be 500 nm or less. EXAMPLES
[0035] The effects of the present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples.
[0036] <Preparation of pretreatment agent> Pretreatment agents 1 to 24 were prepared by adding compound (A) and a metal acid ion (B) source to water to give a predetermined molar concentration as shown in Table 1. In addition, the following A1 to A8 and B1 to B4 were used as the compound (A) and metal acid ion (B) source in the preparation of the pretreatment agents. The pH of the pretreatment agents was 10. A1: Ethylenediamine Tokyo Chemical Industry Co., Ltd. A2: Diethylenetriamine Tokyo Chemical Industry Co., Ltd. A3: Triethylenetetramine Tokyo Chemical Industry Co., Ltd. A4: Tetraethylenepentamine Tokyo Chemical Industry Co., Ltd. A5: Pentaethylenehexamine Tokyo Chemical Industry Co., Ltd. A6: N,N'-bis(2-aminoethyl)-1,3-propanediamine Tokyo Chemical Industry Co., Ltd. A7: N,N'-bis(3-aminopropyl)ethylenediamine Tokyo Chemical Industry Co., Ltd. A8: Epomin (registered trademark) SP-200, Nippon Shokubai Co., Ltd. B1: Sodium molybdate dihydrate Junsei Chemical Co., Ltd. B2: Ammonium molybdate (tetrahydrate) Kishida Chemical Co., Ltd. B3: Sodium tungstate dihydrate, Nacalai Tesque, Inc. B4: Ammonium paratungstate, Nippon Inorganic Chemical Industry Co., Ltd.
[0037] [Table 1]
[0038] [Preparation of painted metal materials] <Metal materials> The metal material is cold-rolled mild steel plate (SPC) specified in JIS G3141:2011. C: Thickness 0.8 mm), hot-dip galvanized steel sheet specified in JIS G3302:2012 (SGCC: thickness 0.8mm), alloying melting specified in JIS G3302:2012 Galvanized steel sheet (SCGA: thickness 0.8 mm) and JIS H4000:2014 The specified aluminum alloy plates (A6061: thickness 0.8 mm) were prepared and cut to a size of 70 mm length x 150 mm width. In the evaluation of the painted metal material described below, the surface with burrs on the edge of the metal material was used as the evaluation surface. The height of the burrs was approximately 100 μm. <Degreasing treatment for metal materials>
[0039] Various metal materials were immersed in an alkaline degreasing agent [an aqueous solution of Fine Cleaner E2093 (manufactured by Nihon Parkerizing Co., Ltd.) in which agent A was mixed with agent B at 13 g / L and 11 g / L in water] at 45°C for 2 minutes to remove oil and dirt from the surfaces of the metal materials. The surfaces of the metal materials were then washed with water.
[0040] <Pretreatment for metal materials> As shown in Tables 2 and 3, various metal materials that had been subjected to the above-mentioned degreasing treatment were pretreated by immersing them in various pretreatment agents shown in Table 1 at 25° C. for 90 seconds.
[0041] <Chemical conversion treatment> Various metal materials that had been subjected to the above-mentioned degreasing treatment and pretreatment were immersed in a 50 g / L aqueous solution of zirconium conversion treatment solution (Palcido 1500, manufactured by Nippon Parkerizing Co., Ltd.) at 40°C for 120 seconds to produce metal materials on which a zirconium conversion coating was formed. In Example 25, various metal materials that had been degreased were immersed for 120 seconds at 40°C in an aqueous solution in which 100 mg / L of KBM-603 (Shin-Etsu Chemical Co., Ltd.) was added to a 50 g / L aqueous solution of zirconium conversion treatment solution (Pulseed 1500, manufactured by Nihon Parkerizing Co., Ltd.) to produce metal materials on which a zirconium conversion coating was formed. In Example 26, various metal materials that had been degreased were immersed in a 50 g / L aqueous solution of zirconium conversion treatment solution (Palseed 1500, manufactured by Nihon Parkerizing Co., Ltd.) and copper sulfate ( II) 4) In an aqueous solution containing 10 mg / L copper pentahydrate (Nacalai Tesque, Inc.) The metal material was immersed at 0°C for 120 seconds to produce a zirconium conversion coating.
[0042] <Electrodeposition coating treatment for metal materials with chemical conversion coating> The metal material on which the zirconium conversion coating was formed was washed with pure water, and then electrolysis was performed for 180 seconds at a voltage of 200 V using various metal materials as cathodes and a cationic electrodeposition paint (GT-100, manufactured by Kansai Paint Co., Ltd.) to deposit the coating film components on the entire surface of the metal material. Thereafter, the metal material was washed with pure water and baked for 20 minutes at 170°C (PMT: maximum temperature of the metal material during baking) to prepare a coated metal material. The coating film thickness of the coated metal material was adjusted to 20 μm. The coated metal materials prepared at this time were designated as Examples 1 to 26 and Comparative Examples 1 to 4, as shown in Tables 2 and 3. In Comparative Example 1, no chemical pretreatment was performed.
[0043] [Table 2]
[0044] [Table 3]
[0045] <Corrosion resistance evaluation> In order to confirm the corrosion resistance of the edge burrs of each of the coated metal materials prepared in Examples 1 to 26 and Comparative Examples 1 to 4, each coated metal material was placed in a combined cycle tester and subjected to a combined cycle test for 100 cycles in accordance with JASO-M609-91. After application, the maximum bulge width from the burr generated during cutting was measured, and the corrosion resistance of the edge burr was evaluated according to the following evaluation criteria. Note that in order to evaluate the edge burr, tape sealing was not applied to the edges and backsides of the various coated metal materials. The results are shown in Tables 4 and 5. Evaluation criteria B and above were considered to be in the practical range. (Evaluation Criteria) S: The maximum bulge width is less than 1.0 mm. (Best) A: The maximum bulge width is 1.0 mm or more and less than 1.5 mm. B: The maximum bulge width is 1.5 mm or more and less than 2.5 mm. C: The maximum bulge width is 2.5 mm or more and less than 5.0 mm. D: The maximum bulge width is 5.0 mm or more.
[0046] [Table 4]
[0047] [Table 5]
Claims
[Claim 1] A treatment agent used in pretreatment of a chemical conversion treatment for forming a chemical conversion coating on the surface or surface of a metal material, the treatment agent comprising: One or more compounds (A) selected from compounds having a structure represented by the following formula (I) and having two or more primary amino groups; The present invention relates to a method for preparing a solution containing a metal ion (B) selected from a molybdate ion and a tungstate ion, and water, and having a pH of 7 or more and 10 or less; The chemical conversion treatment is selected from a zirconium chemical conversion treatment, a titanium chemical conversion treatment, a hafnium chemical conversion treatment, and a vanadium chemical conversion treatment. -(NH-CH 2 -CH 2 ) n - ・・・(I) Here, n is an integer of 1 or more.
Citation Information
Patent Citations
Treatment of surface on formed material combining aluminum and steel material and treating solution
JP1992218681A
Production of galvanized steel sheet excellent in pressability, chemical convertibility and adhesive compatibility
JP1996296058A
Method for applying a chemical conversion coating to a metal surface and solution therefor
JP1998508659A
Galvanized steel sheet for chemical conversion, its manufacturing method, and chemically treated steel sheet
JP2006265578A
Method for producing high-strength cold-rolled steel sheet excellent in corrosion resistance after coating
JP2007217743A
